Analisis Keandalan untuk Menentukan Interval Penggantian Komponen Slotter (Fine Adjusting Block dan Back Knife Transmission Gear) pada Mesin Flexo Ps 429â€ - Yulianto, Fery; Nilasari, Vicka Annisa (Jurnal Teknik Industri, 2008)
PT. Prima Box Adiperkasa Pandaan is a manufacturing company which producing cartoon box which the production processing is mostly use an automatic machine. The Flexo PS 429 is a machine which playing an important role in cutting and printing procession which often being damage, as a consequence it need to be supported with the program and activity of a regular treatment of the machines production. The problem that is faced was how to determine the optimal time interval of to replace the component so the productions can be process according to the target which has been specified. The objective of the research is to determine the time interval to replace the slotter component (back knife transmission gear and fine adjusting block) as an effort to prevent the damage the replacement cost which optimal with the reliability level above 70% (> = 0.7). The model which used to determine the time interval replacement component in this research is use an age replacement model with the minimum cost criteria. In this method of component replacement according to the international which have been done before the damage happen. From the obtained result of data analysis that the optimal international replacement of the back knife transmission gear component is 18 days with the prevention cost replacement is equal to Rp29,870 and the reliability is 0.832 (83.2%). Where as for fine adjusting block component in 12 days interval with the prevention cost replacement is equal to 16.970 and reliability is 0.925 (92.5). So at 12 month by conducting a cost saving prevention replacement of the back knife transmission gear company is 7,06% or equal to Rp681,001.44. For fine adjusting block component, by conducting a cost â€“ saving is 49.66% or equal Rp5.002.866,7.